German and East Asian Perspectives on Corporate and Capital Market Law Investors versus Companies - Fleischer, Holger; Fleischer, Holger (Mohr Siebeck, 2023)
This volume is based on updated presentations delivered at a symposium held in 2017 at Seoul National University. It follows two earlier conference volumes and shares their goal to stimulate the scholarly exchange between company law academics in Germany, China, Japan and South Korea which can be traced back to the late nineteenth century. Contributions from all four jurisdictions include papers on shareholder activism and the disclosure of substantial shareholdings as well as studies on takeover law addressing key questions such as the mandatory bid rule, control premiums, hostile takeovers and pre- and post-bid defences.